Optimization Of Wind Barriers For The Minimization Of Mirror Soiling In A Parabolic Trough Collector Plant - Moghimi Ardekani, Mohammad (University of Pretoria, 2021)
Dissertation (MEng (Mechanical Engineering))--University of Pretoria, 2021.